2021
DOI: 10.3389/fonc.2021.654251
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Robotic Radiosurgery for the Management of Spinal Ependymomas

Abstract: BackgroundEpendymomas are rare neoplasms of the central nervous system (CNS), usually localized intracranially and most commonly diagnosed in children. Spinal ependymomas are more frequent in young adults. They are either primary lesions or manifest as disseminated seeding of cranial tumors. Data on the management of spinal ependymoma lesions remain scarce, especially concerning stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT). The purpose of this study is to report the treatment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The first report, a case report of a recurrent vestibular schwannoma treated with RRS in a 13-year-old boy, was published in 2000 [ 13 ]. The latest study addressed the treatment of spinal ependymomas, included two pediatric cases, and was published in 2021 [ 14 ]. The studies reviewed herein reported on a broad variety of CNS entities, including arteriovenous malformations (AVM), neuroblastoma, ependymoma, vestibular schwannoma, chordoma, craniopharyngioma (CP), fibrosarcoma, hamartoma, pineal germinoma, pituitary adenoma, optic pathway or pilocytic glioma, Ewing sarcoma, atypical teratoid rhabdoid tumor (ATRT), and medulloblastoma.…”
Section: Resultsmentioning
confidence: 99%
“…The first report, a case report of a recurrent vestibular schwannoma treated with RRS in a 13-year-old boy, was published in 2000 [ 13 ]. The latest study addressed the treatment of spinal ependymomas, included two pediatric cases, and was published in 2021 [ 14 ]. The studies reviewed herein reported on a broad variety of CNS entities, including arteriovenous malformations (AVM), neuroblastoma, ependymoma, vestibular schwannoma, chordoma, craniopharyngioma (CP), fibrosarcoma, hamartoma, pineal germinoma, pituitary adenoma, optic pathway or pilocytic glioma, Ewing sarcoma, atypical teratoid rhabdoid tumor (ATRT), and medulloblastoma.…”
Section: Resultsmentioning
confidence: 99%
“…Stereotactic radiation therapy (SRT) can increase tumor dose and reduce exposure to normal tissue, resulting in higher tumor control rates and lower normal tissue complications ( 1 3 ). As a special device for SRT, CyberKnife is increasingly applied in the treatment of spinal tumors in modern radiotherapy ( 4 6 ). To ensure the stability of the patient’s position during treatment, CyberKnife is used to treat tumors in the supine position.…”
Section: Introductionmentioning
confidence: 99%